MENINGKATKAN KETERAMPILAN SISWA MEMBUAT KALIMAT SEDERHANA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PICTURE AND PICTURE BERBASIS KEARIFAN LOKAL - Nur Dwiastutiningsih Sumartini (Khazanah Pendidikan, 2015)
The general objective of classroom action research is to improve student learning outcomes in Indonesian language teaching while the specific goal to improve students' skills in making simple sentences through Learning Model Picture and Picture-Based Local Wisdom in Class III State Elementary School Kalisube first semester of school year 2015 / 2016. Subjects were all third grade students of State Elementary School District of Banyumas Kalisube first semester of academic year 2015/2016 the number of students 31 students consisting of 17 male students and 14 female students. Implementation of Class Action Research through two cycles of the first cycle and the second cycle. Research shows that learning outcomes Indonesian material to make a simple sentence on the initial conditions is very low at an average value only reaches 72.1 class that is still under KKM (limit class completeness) are 75. Then once held the action in the first cycle by means teaching teachers use learning model Picture and Picture-Based Local Wisdom average value that was originally only 72.1 rose to 74 as well as learning the liveliness of 61.3%. After holding action on the second cycle with the teacher in the learning using learning model Picture and Picture- Based Local Wisdom with some pictures of puppet characters Banyumas held by all the students the value of the average grade in the first cycle 74 rose to 95 and activeness study reached 87, 1%. The conclusion in the classroom action research based on the study of theory and empirical data turns with use of the learning model Picture and Picture-Based Local Wisdom increased. Thus the hypothesis that the researchers propose in this Class Action Research is “proven”. Keywords: sentence-making skills, Picture and Picture-Based Local Wisdom learning models, Banyumas puppet